1981
DOI: 10.1099/0022-1317-55-2-343
|View full text |Cite
|
Sign up to set email alerts
|

Cytopathic Effects in Mouse Neuroblastoma Cells during a Non-permissive Infection with a Mutant of Vesicular Stomatitis Virus

Abstract: SUMMARYMorphological changes were extensive following infection of murine neuroblastoma N-18 cells with a temperature-sensitive (ts) mutant of vesicular stomatitis virus (VSV), G31 (complementation group III), and incubation at 39 °C, a non-permissive condition for virion maturation. Incubation for 24 h after infection resulted in extensive morphological degeneration of mitochondria with over 80 % of the mitochondria having degenerated. Mitochondrial function, as determined by Janus green B supravital staining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1982
1982
2002
2002

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…This fusion of cells resembled the status of spongiosus described in kuru patients and in other slow virus diseases (Gibbs et al, 1968), and AIDS patients have been shown to have multinucleated cells in their CNS (Navia et al, 1986). Cultured neuroblastoma cells fused when they were infected with tsG31 VSV and incubated at a non-permissive temperature for virus replication (Hughes et al, 1979a;Dille et al, 1981).…”
Section: Introductionsupporting
confidence: 52%
“…This fusion of cells resembled the status of spongiosus described in kuru patients and in other slow virus diseases (Gibbs et al, 1968), and AIDS patients have been shown to have multinucleated cells in their CNS (Navia et al, 1986). Cultured neuroblastoma cells fused when they were infected with tsG31 VSV and incubated at a non-permissive temperature for virus replication (Hughes et al, 1979a;Dille et al, 1981).…”
Section: Introductionsupporting
confidence: 52%
“…The same may be true for different strains or mutants of VSV (6,8). Previous work has suggested a permanent reduction in serotonin (20,21) after VSV infection.…”
Section: Discussionmentioning
confidence: 88%
“…Cell fusion has only been shown with nervous system-derived cells during a non-permissive infection (Hughes et al, 1979a;DiIle et al, 1982). The fusion requires the synthesis and expression of the VSV glycoprotein (G) on the infected cell surface membrane and is inhibited by the addition of glucosamine or tunicamycin that interfere with glycosylation (Hughes et al, 1979a, Dille et al, 1981.…”
Section: Introductionmentioning
confidence: 99%